2003
DOI: 10.1128/aem.69.7.3777-3783.2003
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Expression System for Site-DirectedMutagenesis of the LantibioticMersacidin

Abstract: The lantibiotic (i.e., lanthionine-containing antibiotic) mersacidin is an antimicrobial peptide of 20 amino acids which is produced by Bacillus sp. strain HIL Y-85,54728. Mersacidin inhibits bacterial cell wall biosynthesis by binding to the precursor molecule lipid II. The structural gene of mersacidin (mrsA) and the genes for the enzymes of the biosynthesis pathway, dedicated transporters, producer self-protection proteins, and regulatory factors are organized in a biosynthetic gene cluster. For site-direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 33 publications
7
69
0
Order By: Relevance
“…1) (17,18,29,30). Importantly, the six-aminoacid-containing MeLan B-ring in Hal␣, which is believed to be important for lipid II binding in mersacidin's C-ring (32), is conserved including the invariant and essential Glu within this ring (33). This MeLan ring is also found in the ␣͞A1-peptides of lacticin 3147 (21), plantaricin W (17), staphylococcin C55 (18), Smb (29), and BHT-A (30), as well as in the A-ring of the lacticin 481 subgroup of single component lantibiotics (3).…”
Section: Discussionmentioning
confidence: 99%
“…1) (17,18,29,30). Importantly, the six-aminoacid-containing MeLan B-ring in Hal␣, which is believed to be important for lipid II binding in mersacidin's C-ring (32), is conserved including the invariant and essential Glu within this ring (33). This MeLan ring is also found in the ␣͞A1-peptides of lacticin 3147 (21), plantaricin W (17), staphylococcin C55 (18), Smb (29), and BHT-A (30), as well as in the A-ring of the lacticin 481 subgroup of single component lantibiotics (3).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has also been associated with a number of other engineered lantibiotics, especially those in which modified amino acids are altered (33). It has been suggested that inhibition of the enzymes of the modification machinery may be the most likely explanation (34). Although nonproduction of LtnA1(7A) and (7V) meant that it was not possible to determine to what extent a D to L conversion would affect the relative activity of LtnA1, it was apparent that significant levels of relative activity were retained upon the replacement of D-alanine with nonchiral amino acids.…”
Section: Identification Of a Dha Reductase Ltnj Responsible For The Smentioning
confidence: 99%
“…19 Very surprisingly, this mutation did not abolish activity, unlike with the equivalent mersacidin and haloduracin-a mutants that were both strongly affected by this change. 8,[20][21][22] Other mutants in ring A were found to retain activity, suggesting there is some degree of flexibility in the amino acids of this ring. 23 Mutagenesis has been used to produce weakly active analogs containing the changes S4T, H8P, Q20T and truncation at S27.…”
Section: Lacticin 481mentioning
confidence: 99%
“…An initial limited study produced the mutants F3L, S16I and E17A, all of which were found to be inactive or very weakly active. 21 A subsequent systematic production of mersacidin analogs via mutagenesis yielded a far larger number of mutants. 22 Three libraries were designed in which amino acids were substituted, inserted or deleted.…”
Section: Structure-activity Relationships Of Lantibiotic Peptides Ac mentioning
confidence: 99%